Three-and-a-Half Million U.S. Employees Have Been Mislaid: Or, an Explanation of Unemployment, 1934-1941 - Darby, Michael R. (Journal of Political Economy, 1976)
A major conceptual error in the standard BLS and Lebergott unemployment estimates for 1930-43 is reported. Emergency workers (employees of government contracyclical programs such as WPA) were counted as unemployed on a normal-jobs-to-be-created instead of job-seekers unemployment definition. For 1933-41, the corrected unemployment levels are reduced by 2-3.5 million people and the rates by 4-7 percentage points. The corrected data show strong movement toward the natural unemployment rate after 1933 and are very well explained by an anticipations-search model using annual full-time earnings.